How not to die : surprising lessons on living longer, safer, and healthier from America's favorite medical examiner - Garavaglia, Jan (Crown Publishers, 2008)
Thousands of people make an early exit each year and arrive on medical examiner Jan Garavaglia's table. What is particularly sad about this is that many of these deaths could easily have been prevented. Although Dr. Garavaglia, or Dr. G, as she's known to many, could not tell these individuals how to avoid their fates, we can benefit from her experience and profound insight into the choices we make each day. In this book, Dr. G acts as a medical detective to identify the often-unintentional ways we harm our bodies, then shows us how to use that information to live better and smarter. She provides startling tips on how to make wise choices so that we don't have to be seen by this doctor, or someone like her, for a good long time--From publisher description.